2010
DOI: 10.1002/hbm.21120
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala and hippocampus volumetry and diffusivity in relation to dreaming

Abstract: Microstructural analyses by MRI brain scans and by DTI analysis of MR images were used to investigate the possible relationship between deep gray matter structures (amygdala and hippocampus) and dreaming in healthy subjects. Thirty-four subjects ranging in age 20s to 70s underwent to a MRI protocol for the assessment of volume and mean diffusivity (MD) in the amygdala and hippocampus and were asked to fill out a dream diary via audiotape recording upon morning awakening for two weeks. Multiple regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 80 publications
(84 reference statements)
10
64
0
Order By: Relevance
“…In our opinion, the models based on physiological activation (Antrobus 1991;Koulack and Goodenough 1976;Rosenblatt et al 1992;Zimmerman 1970) and on shared mechanisms across wakefulness and sleep (De Gennaro et al 2011;Marzano et al 2011a;Scarpelli et al 2015a) are not mutually exclusive. A bulk of empirical evidence had made it clear that both the mechanisms underlying the encoding of episodic memory in sleep and wakefulness (De Gennaro et al 2011;Domhoff 2003;Marzano et al 2011a;Scarpelli et al 2015a;Schredl & Hoffmann 2003) and a specific electrophysiological background during sleep could affect the retrieval of the sleep mentation (De Gennaro et al 2010;Schredl 2009).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In our opinion, the models based on physiological activation (Antrobus 1991;Koulack and Goodenough 1976;Rosenblatt et al 1992;Zimmerman 1970) and on shared mechanisms across wakefulness and sleep (De Gennaro et al 2011;Marzano et al 2011a;Scarpelli et al 2015a) are not mutually exclusive. A bulk of empirical evidence had made it clear that both the mechanisms underlying the encoding of episodic memory in sleep and wakefulness (De Gennaro et al 2011;Domhoff 2003;Marzano et al 2011a;Scarpelli et al 2015a;Schredl & Hoffmann 2003) and a specific electrophysiological background during sleep could affect the retrieval of the sleep mentation (De Gennaro et al 2010;Schredl 2009).…”
Section: Discussionmentioning
confidence: 94%
“…A bulk of empirical evidence had made it clear that both the mechanisms underlying the encoding of episodic memory in sleep and wakefulness (De Gennaro et al 2011;Domhoff 2003;Marzano et al 2011a;Scarpelli et al 2015a;Schredl & Hoffmann 2003) and a specific electrophysiological background during sleep could affect the retrieval of the sleep mentation (De Gennaro et al 2010;Schredl 2009). On the one hand, frontal theta oscillations during REM sleep (Marzano et al 2011a;Scarpelli et al 2015a) and lower alpha power during NREM sleep (Esposito et al 2004;Marzano et al 2011a) predict the subsequent DR, and these patterns resemble the EEG pattern observed in wakefulness during a successful performance in episodic memory tasks (Addante et al 2011;Guderian et al 2009;Klimesch 1996Klimesch , 1999Klimesch et al 1996).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Dream Bizarreness scale (Hobson et al, 1987) was used to score the material and calculate: bizarreness intensity (BI; the number of bizarre events in the domains of plot, cognition and affect); and bizarreness density (BD; calculated by dividing BI by the report word count). Emotional load (EL), without distinction between positive or negative affects, and visual vividness (VV) were also independently scored by the two raters on six-point Likert rating scales for each narrative (De Gennaro et al, 2011). All scripts were then read and recorded by an experimenter (R.R.)…”
Section: Participants and Data Collectionmentioning
confidence: 99%
“…Studies of cerebral blood flow and metabolism during rapid eye movement (REM) sleep suggested a relatively reduced activity in precuneus, dorsolateral prefrontal, posterior cingulate and parietal cortex, with increased activations in limbic and paralimbic regions including amygdala, hippocampus, anterior cingulate and orbitofrontal cortex (Dang-Vu, 2012). The limbic involvement is confirmed by the observation that volumes and microstructure of left amygdala inversely correlate, and volumes of right hippocampus directly correlate, with bizarreness in dream reports (De Gennaro et al, 2011). Nevertheless, a critical involvement of cortical areas in building the implausible story representation of dreams is suggested by the observation that some cortical lesions can impair or completely block dreaming (Nir and Tononi, 2010), also supporting the hypothesis that the modular architecture of brain functions is maintained during dreams (Desseilles et al, 2011).…”
Section: Introductionmentioning
confidence: 98%